Penerapan E-Office di Lingkungan Politeknik STIA LAN Bandung - Nur Imam Taufik; Reni Wijayanti (STMIK Budi Darma, 2021)
The application of E-Office in office activities and service fulfillment at the Polytechnic of STIA LAN Bandung creates information technology-based services. The application of e-office information technology to support e-government has a positive impact on improving employee performance in the Polytechnic of STIA LAN Bandung environment in Bandung. The available applications are also quite diverse, starting from office administration contained in the FiSH (file Sharing) and Andalan (Archive and mail administration) applications, learning services carried out through the Microsoft Team and registration services through the PCMB Online information system. This study will elaborate on the use of E-Office as an online service medium used at the Polytechnic of STIA LAN Bandung.